2019
DOI: 10.3389/fendo.2019.00506
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Distributor Proteins During Development in Vertebrates

Abstract: Thyroid hormones (THs) are ancient hormones that not only influence the growth, development and metabolism of vertebrates but also affect the metabolism of (at least some) bacteria. Synthesized in the thyroid gland (or follicular cells in fish not having a discrete thyroid gland), THs can act on target cells by genomic or non-genomic mechanisms. Either way, THs need to get from their site of synthesis to their target cells throughout the body. Despite being amphipathic in structure, THs are lipophilic and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 88 publications
1
30
0
Order By: Relevance
“…Our study also found that newborns born via C-section delivery had higher cord serum FT3 than those born via vaginal delivery. This might be due to the decreased levels of thyroid hormone distributer proteins (THDPs) which include albumin, transthyretin (TTR), and thyroxine-binding globulin (TBG) (53). As albumin, TTR and TBG are negative acute phase plasma proteins, all of them will be down-regulated in situations of stress or surgery (53), resulting in increased FT3.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that newborns born via C-section delivery had higher cord serum FT3 than those born via vaginal delivery. This might be due to the decreased levels of thyroid hormone distributer proteins (THDPs) which include albumin, transthyretin (TTR), and thyroxine-binding globulin (TBG) (53). As albumin, TTR and TBG are negative acute phase plasma proteins, all of them will be down-regulated in situations of stress or surgery (53), resulting in increased FT3.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, there is clear evidence that increased TH production/release induces increases in metabolic rate ( 2 ), weight loss ( 3 ), and cardiac output ( 4 ), while decreased TH production/release leads to opposite effects. In all vertebrates, THs are key hormones that influence a number of physiological processes including growth, development/morphogenesis, and metabolism ( 5 ). However, in fish, the role of the thyroid is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating TSH acts on the thyroid to produce predominantly T4, which is converted to its active form triiodothyronine (T3) in peripheral tissue, and the access of thyroid hormones to their target tissues is influenced by TBG. Other liverexpressed plasma proteins, transthyretin and albumin, also bind thyroid hormones in the human and rodent (15 and 10% of human plasma T4, respectively) but with much lower affinity than TBG (Rabah et al 2019) and they do not appear to be required for thyroid hormone homeostasis in humans (Woeber & Ingbar 1968).…”
Section: Postnatal Maturation Of the Hpt Axismentioning
confidence: 99%